2016
DOI: 10.3389/fmicb.2016.01707
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Extreme Environmental Conditions Favor the Prevalence of Endospore-Forming Firmicutes

Abstract: Environmental conditions unsuitable for microbial growth are the rule rather than the exception in most habitats. In response to this, microorganisms have developed various strategies to withstand environmental conditions that limit active growth. Endospore-forming Firmicutes (EFF) deploy a myriad of survival strategies in order to resist adverse conditions. Like many bacterial groups, they can form biofilms and detect nutrient scarcity through chemotaxis. Moreover, within this paraphyletic group of Firmicutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(66 citation statements)
references
References 72 publications
4
51
1
1
Order By: Relevance
“…Our results showed that Bacillales, the order within the class Bacilli, overwhelmingly dominated in relative abundance in the intermediate pattern (8-48 h) and were largely responsible for differences in microbial response to flooding, although the detected richness of the community that responded intermediately was less than that of results from the study of Placella et al [6]. The lesser community richness in the intermediate pattern may depend on, not only the different soil with distinct properties and indigenous microorganisms, but also on the eventual water conditions, since abrupt flooding of dry soil in our experiment may delay and impede the growth of taxa which should have grown intermediately under favorable moisture conditions, such as some other species of Firmicutes [59]. This indicates the potential effects of Bacilli, the intermediate responder, on ultimate microbial ecology and soil ecosystem functioning due to their particular ecological function such as the production of hydrolytic enzymes breaking intermediate-sized polymers into monomers [6].…”
Section: Potential Role Of Bacilli In the Trajectory Of The Bacterialcontrasting
confidence: 65%
See 1 more Smart Citation
“…Our results showed that Bacillales, the order within the class Bacilli, overwhelmingly dominated in relative abundance in the intermediate pattern (8-48 h) and were largely responsible for differences in microbial response to flooding, although the detected richness of the community that responded intermediately was less than that of results from the study of Placella et al [6]. The lesser community richness in the intermediate pattern may depend on, not only the different soil with distinct properties and indigenous microorganisms, but also on the eventual water conditions, since abrupt flooding of dry soil in our experiment may delay and impede the growth of taxa which should have grown intermediately under favorable moisture conditions, such as some other species of Firmicutes [59]. This indicates the potential effects of Bacilli, the intermediate responder, on ultimate microbial ecology and soil ecosystem functioning due to their particular ecological function such as the production of hydrolytic enzymes breaking intermediate-sized polymers into monomers [6].…”
Section: Potential Role Of Bacilli In the Trajectory Of The Bacterialcontrasting
confidence: 65%
“…However, most Actinobacteria were found belonging to the delayed pattern in the total (DNA-based) community, which was possibly explained by a competitive disadvantage during the early hours of rewetting [10]. Secondly, intermediate responders, both in the total and the potentially active community, were generally Firmicutes, a phylum well known for their ability to produce a highly resistant endospores produced in stressful environment [59]. When transferred to favorable conditions such as rewetting from drought, spores could synthesize RNA quickly to recover and grow, then increase in relative abundance.…”
Section: Potential Role Of Bacilli In the Trajectory Of The Bacterialmentioning
confidence: 97%
“…High-altitude wetland microbial communities have been considered as a hotspot of microbial life (Albarracín et al, 2015;Dorador et al, 2013); however, scarce information is available concerning the factors potentially driving this diversity. Limiting environmental factors, such as, temperature, pH, and mineral composition could favor the presence of certain groups of microorganisms, such as endospore-forming firmicutes in extreme environments (Filippidou et al, 2016). Moreover, factors like salinity could generate niche partitioning among functional groups (Oren, 2001) and salinity plus nutrients were suggested to limit different biotic components of high altitude aquatic environments such as, lakes and lagoons (Márquez-García et al, 2009).…”
mentioning
confidence: 99%
“…In sharp contrast, the apparently unhygienic surface conditions of the wooden cutting boards in wet markets, in combination with Hong Kong's high ambient temperature and high relative humidity conditions, are conducive to pathogenic microbial proliferation on freely displayed meat products [4]. It has been reported that certain bacteria belonging to phylum Firmicutes can survive at low temperature [40,41]. For example, some species belonging to this bacterial group have survival mechanisms to withstand harsh environmental conditions [42], such as by producing endospores at low temperatures, which then remain dormant until conditions become favourable [43,44].…”
Section: Microbial Community Profile In Meat Samplesmentioning
confidence: 99%